If A = ax − 2ay − 3az B = 2ax + ay − az and C = ax + 3ay − 2az: find: (a) |(AxB)xC| ; (b) A.(BxC) ; (c) area of the parallelogram formed by A and B
If A = ax − 2ay − 3az B = 2ax + ay − az and C = ax + 3ay − 2az: find: (a) |(AxB)xC| ; (b) A.(BxC) ; (c) area of the parallelogram formed by A and B
Related questions
Question
If A = ax − 2ay − 3az B = 2ax + ay − az and C = ax + 3ay − 2az: find:
(a) |(AxB)xC| ; (b) A.(BxC) ; (c) area of the parallelogram formed by A and B
Expert Solution

This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 2 steps with 2 images
